Assessing the Economic Burden and Health Care Utilizations of U.S. Veteran Patients with Schizophrenia - Lin Xie; M. Furaha Kariburyo; Juan Du; Yuexi Wang (Journal of Health Economics and Outcomes Research, 2013)
# Objective To examine the economic burden and health care utilizations of schizophrenia in the U.S. veteran population.